PERSPEKTIF GURU TERHADAP IMPLEMENTASI KURIKULUM DEEP LEARNING DAN DAMPAKNYA TERHADAP PEMBELAJARAN MATEMATIKA DI KELAS II SDN 1 PATALAN - Astutik, Ika Dwi; Aqidatul Munfariqoh; Anna Mariyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine teachers' opinions regarding the implementation of the Deep Learning Curriculum and its impact on the mathematics learning process in grade II of SDN 1 Patalan. The research approach used was descriptive qualitative. Data were obtained through in-depth interviews with grade II teachers and the principal, direct observation of mathematics learning, and collection of learning tool documents. Data analysis was conducted using the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and conclusion drawing. This study shows that teachers have a positive view of the Deep Learning method. They believe this approach can help students understand concepts more deeply, increase student participation, and enrich the learning process in a more meaningful and enjoyable way. Its implementation has had positive impacts such as increased understanding of mathematical concepts, increased participation in learning, increased enthusiasm for learning, and critical thinking skills. However, teachers face several obstacles, such as a lack of understanding of the Deep Learning concept, limited available media and learning resources, and differences in student ability levels. This study suggests that teachers need to receive ongoing training and schools must have adequate facilities.